AWARENESS ON NUT ALLERGIES AMONG SCHOOL STUDENTS - Trisha,; Ganapathy, Dhanraj; Sasanka, Keerthi (International Journal of Psychosocial Rehabilitation, 2020)
The role of the immune system is to protect the body from germs and diseases. A food allergy is the over reaction by the immune system to a food protein. People are allergic to many kinds of food, majorly nuts. Anaphylaxis is a severe allergic reaction that comes on quickly and could even cause death in certain cases. The aim of this study was to assess awareness on nut allergies and to study the already existing knowledge on the topic among school students. Self-administered questionnaire was created based on the awareness of the presence of nut allergy, their signs and symptoms. The questionnaire was distributed by person as fill out sheets at a nearby school. The study population included 200 school students belonging to the age group of 8 to 16 and years. The questions were carefully studied, and corresponding answers were marked by the participants. The data was collected and statistically analyzed. According to the survey results, about 81% of the total school population were aware about the presence of nut allergy. 85% voted prevention is better to manage nut allergy.70.8% were aware of signs and symptoms of nut allergy .63% said their family members or friends have some kind of allergy to various nuts. Most of the school students had knowledge and were aware about the presence of nut allergies, but more awareness has to be spread as the allergies could turn out to be very serious or even fatal and can only be controlled only through prevention.